BILLION DOLLAR WHALE : KISAH SEBENAR JHO LOW DAN SKANDAL 1MDB - Wright, Tom
What does it take to steal $5 billion? In 2009, with the dust yet to settle on the financial crisis, a mild-mannered Wharton grad set in motion a fraud of unprecedented gall and magnitude--one that would come to symbolize the next great threat to the